Liquid Crystalline Polymers Volume 2--Processing and Applications - Thakur, Vijay Kumar; Kessler, Michael R. (Springer International Publishing : Imprint: Springer, 2015)
This book introduces various applications of liquid crystalline polymers as the emerging new class of high performance novel materials.  The authors detail the advantageous properties of these LCs including optical anisotropic, transparency, and easy control over structure.  This interdisciplinary work includes valuable input from international projects with special focus on the use of liquid crystalline polymers and/or nanocomposites.